2015
DOI: 10.1177/0091450915608446
|View full text |Cite
|
Sign up to set email alerts
|

Mental States of Addiction

Abstract: An increasing number of studies have examined lay meanings of addiction. The purpose of this study was to explore whether a generalized conception of an addiction mind-set was evident in the beliefs of a sample of 1,062 Norwegian adults responding to an online survey. The respondents were given a rating task in the following form: “Addiction to [substance/behavior] is/represents [descriptive term].” For each of the nine different addictive behaviors (cocaine, cannabis, alcohol, gambling, smoking, amphetamine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The mean age of the sample was 47, SD = 14; 50% were women. Results from the same survey have previously been reported in Melberg et al (2013), Rise et al (2014, 2015), but none of the present analyses have been published before. None of the studies reported in the present article required ethics approval per our institution’s guidelines and Norwegian law.…”
Section: Methodsmentioning
confidence: 55%
See 1 more Smart Citation
“…The mean age of the sample was 47, SD = 14; 50% were women. Results from the same survey have previously been reported in Melberg et al (2013), Rise et al (2014, 2015), but none of the present analyses have been published before. None of the studies reported in the present article required ethics approval per our institution’s guidelines and Norwegian law.…”
Section: Methodsmentioning
confidence: 55%
“…As an example, the participants rated the level of agreement with the statement “Addiction to Cocaine is/represents…reduced willpower”. The descriptors were based on an informal survey of the literature and reflected conceptualizations by lay people and scientists (see Rise et al, 2015).…”
Section: The Present Researchmentioning
confidence: 99%
“…"Addiction is a slippery concept of which the meaning, content, and definitions change according to cultural, political, historical, and finally scientific underpinnings" (RISE; HALKJELSVIK; KOVAČ, 2015). Based on this definition on addiction can be understood the alteration across countries about cultural and social norms on drug use, but also there are some common notions on addiction.…”
Section: Drug Addiction In Childrenmentioning
confidence: 99%